Framework for quality assessment of whole genome cancer sequences - Whalley, Justin P.; Buchhalter, Ivo; Rheinbay, Esther; Raine, Keiran M.; Stobbe, Miranda D.; Kleinheinz, Kortine; Werner, Johannes; Beltran, Sergi; Gut, Marta; Hübschmann, Daniel; Hutter, Barbara; Livitz, Dimitri; et al. (Nature Communications, 2020)
Bringing together cancer genomes from different projects increases power and allows the investigation of pan-cancer, molecular mechanisms. However, working with whole genomes sequenced over several years in different sequencing centres requires a framework to compare the quality of these sequences. We used the Pan-Cancer Analysis of Whole Genomes cohort as a test case to construct such a framework. This cohort contains whole cancer genomes of 2832 donors from 18 sequencing centres. We developed a non-redundant set of five quality control (QC) measurements to establish a star rating system. These QC measures reflect known differences in sequencing protocol and provide a guide to downstream analyses and allow for exclusion of samples of poor quality. We have found that this is an effective framework of quality measures. The implementation of the framework is available at: https://dockstore.org/containers/quay.io/jwerner_dkfz/pancanqc:1.2.2.